(untitled) (Economic and Political Thought, 2015)
With the changes in international order, the role of regional co-operation in East-Central Europe in the Polish foreign policy changed too. In the early 1990s, Poland was deeply involved in the development of new structures such as the Central European Initiative, the Council of the Baltic Sea States, and the Visegrad Triangle. The new organisations, to a great extend, were treated instrumentally as a step on the way to rapprochement with the EU and NATO. Poland did not promote its own concepts of developing a new value in this part of Europe and did not aspire to play the role of a regional power based on the new structures either. After the accession to the EU in 2004, the attention of Polish diplomacy focused on the Visegrad Group (V4), which was a key tool in the co-operation of the four countries – Poland, the Czech Republic, Slovakia and Hungary – in the field of their common interests. However, due to big divergences, its role in the areas that are strategic for the security of the region was of little importance. In essence, the regional co-operation in the East-central Europe was important but from the perspective of Warsaw, it was of secondary importance.